Diversity of Mammals in and around of Koshi Tappu Wildlife Reserve - Chhetry, D. Thapa; Pal, J. (Our Nature, 2011)
Though the Koshi Tappu Wildlife Reserve was established for the protection of wild water buffalo, there are other mammals in and around of it due to the presence of different type of habitats like rivers, oxbow lakes, seepage stream, marshlands, floodplains, ponds, swamp forest etc. This paper deals with the study of mammals in and around of Koshi Tappu Wildlife Reserve. Altogether 21 species of mammals belonging to 19 genera and 13 families were found during the study period. Among these 3 occurred commonly, 11 rarely and 7 occasionally at local level. DOI: 10.3126/on.v8i1.4336